1987
DOI: 10.1029/gl014i005p00573
|View full text |Cite
|
Sign up to set email alerts
|

Comment on the Papers “On the influx of small comets into the Earth's upper atmosphere I. Observations and II. Interpretation”

Abstract: Frank et al. [1986a] report that exceptionally dark spots in the ultraviolet images of the sunlit Earth provided by the Spin-scan Auroral Imager (SAI) on the Dynamics Explorer I satellite occur far more frequently than would be expected from Poisson counting statistics, which ordinarily govern the statistical distribution of counts from a photomultiplier tube.Frank et al. [1986b] postulate that the spots, which are usually confined to a single pixel, could be due to obscuration of the photometer field of vie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 4 publications
1
6
0
Order By: Relevance
“…It presents simple, direct, evidence that the dark pixel clusters in the Iowa catalog are the tail of an instrumental noise distribution-they are not produced by atmospheric holes. This same result was demonstrated by Cragin et al (1987) for the original DE-1 small-comet data, who showed that them was no change in the angular size of the purported atmospheric holes with altitude. Thus, 12 years ago, as today, it is shown that the "atmospheric holes" are insmLment noise.…”
Section: Introductionsupporting
confidence: 73%
“…It presents simple, direct, evidence that the dark pixel clusters in the Iowa catalog are the tail of an instrumental noise distribution-they are not produced by atmospheric holes. This same result was demonstrated by Cragin et al (1987) for the original DE-1 small-comet data, who showed that them was no change in the angular size of the purported atmospheric holes with altitude. Thus, 12 years ago, as today, it is shown that the "atmospheric holes" are insmLment noise.…”
Section: Introductionsupporting
confidence: 73%
“…The sensitivity of the event rate to lifetime can be demonstrated with an example in which we assume the dark-spot lifetime is 60 ms and the darkness threshold such that 1 in 1000 pixels is dark. (This is approximately the actual ratio of dark to normal pixels seen by the DE imager [Cragin et al, 1987].) When Earth effectively fills the image frame, a DE Earth image consists of~I0 n pixels.…”
Section: Dessler: the Small-comet Hypothesis ß 361mentioning
confidence: 97%
“…According to the instrument-artifact hypothesis, dark pixels appear in images of the geocorona simply because one in 800 pixels is dark; the observation becomes an instrumental, not a geophysical, effect. With one pixel in 800 randomly turning dark, a statistical fluctuation yielding two adjacent dark pixels is a reasonable expectation [Cragin et al, 1987]. However, a three-dark-pixel event is extremely rare, and four sequentially dark pixels is an almost impossible random coincidence.…”
Section: 3 / Reviews Of Geophysicsmentioning
confidence: 99%
See 1 more Smart Citation
“…critics of the reality of atmospheric holes predict that the rates of atmospheric holes will be unaffected by the spacecraft altitude because they are instrument artifacts[Parks et al, 1997;Dessler, 1991;Cragin et al, 1987]. We refer in this paper to the Parks-Dessler-Cragin hypothesis that the atmospheric holes are instrument artifacts.…”
mentioning
confidence: 99%